The CHK2 kinase is recurrently mutated and functionally impaired in the germline of pediatric cancer patients. Issue 7 (27th December 2022) - Wagener, Rabea; Walter, Carolin; Auer, Franziska; Alzoubi, Deya; Hauer, Julia; Fischer, Ute; Varghese, Julian; Dugas, Martin; Borkhardt, Arndt; Brozou, Triantafyllia
Abstract: Predisposing CHEK2 germline variants are associated with various adult‐type malignancies, whereas their impact on cancer susceptibility in childhood cancer is unclear. To understand the frequency of germline variants in the CHEK2 gene and their impact on pediatric malignancies, we used whole‐exome sequencing to search for CHEK2 variants in the germlines of 418 children diagnosed with cancer in our clinics. Moreover, we performed functional analysis of the pathogenic CHEK2 variants to analyze the effect of the alterations on CHK2 protein function. We detected a CHEK2 germline variant in 32/418 (7.7%) pediatric cancer patients and 46.8% of them had leukemia. Functional analysis of the pathogenic variants revealed that 5 pathogenic variants impaired CHK2 protein function. 6/32 patients carried one of these clearly damaging CHEK2 variants and two of them harbored a matching family history of cancer. In conclusion, we detected germline CHEK2 variants in 7.7% of all pediatric cancer patients, of which a minority but still relevant fraction of approximately 20% had a profound impact on protein expression or its phosphorylation after irradiation‐induced DNA damage. Accordingly, we conclude that CHEK2 variants increase the risk for not only adult‐onset but also pediatric cancer. What's new: Germline mutations in the tumor suppressor gene CHEK2 increase susceptibility to adult‐onset cancer. Whether such variants also contribute to pediatric cancers remains unclear. In this study, the authors investigated the frequency of CHEK2 variants in an unselected cohort of children diagnosed with cancer and in the children's parents. Pathogenic CHEK2 germline variants were detected in 7.7% of children with cancer, about 47% of which were diagnosed with leukemia. Among pediatric cancer patients with germline CHEK2 mutations, nearly one‐fifth suffered impaired CHK2 protein function. The findings suggest that CHEK2 germline variants are predisposing factors to childhood cancer.